2016
DOI: 10.20546/ijcmas.2016.503.083
|View full text |Cite
|
Sign up to set email alerts
|

Role the Employee of Some Biological Stains in Detecting Giardia lamblia among Internal Iraqi Displaced Peoples in Kirkuk Province

Abstract: Giardiasis is waterborne disease which had impact on public health in anywhere of the world, particularly in communities living under low level of sanitation and poor hygienic condition. Selection of such laboratory methods with high accuracy and precise technique recently had great role in reducing the rate of intestinal parasites in general and Giardia lamblia in particular. So the current study was conducted to fulfill this purpose. Three different microscopic based laboratory techniques namely direct doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
4
1
Order By: Relevance
“…In acute cases the picture of liquid diarrhea is mimic to that of IBS, color and even the odor of the positive Giardia stool samples are the same. .The finding rate of giardiasis in current study was not agreed those 7.06 % and 10.31 % recorded in Kirkuk by Salman, et al, 2015b andSalman et al, 2016 respectively in the same Province. Interpretation to this high rate might be due to type of the patients as 21.27% of patients has IBS, while in their studies they take general patients.…”
Section: Resultscontrasting
confidence: 86%
See 1 more Smart Citation
“…In acute cases the picture of liquid diarrhea is mimic to that of IBS, color and even the odor of the positive Giardia stool samples are the same. .The finding rate of giardiasis in current study was not agreed those 7.06 % and 10.31 % recorded in Kirkuk by Salman, et al, 2015b andSalman et al, 2016 respectively in the same Province. Interpretation to this high rate might be due to type of the patients as 21.27% of patients has IBS, while in their studies they take general patients.…”
Section: Resultscontrasting
confidence: 86%
“…Motile organisms can be seen in a wet preparation of a fresh stool however the characteristic morphology is evident in a permanently stained preparation. The records of this parasite were not obvious, because mostly it was considered as non-pathogen, so it was often missed, the two following rates: 0.239 % and 0.126 % of Chilomastix mesnili were recorded in Kirkuk by (Salman et al, 2016 andSalman et al, 2015 b). …”
mentioning
confidence: 99%
“…The researcher showed infection with Giardia lamblia in rural locations was 66.6% higher than in urban locations in humans [61]. In Kirkuk, three different microscopic methods: direct double wet preparation, formal ether and fecal stained smears and reported 10.31% with Giardia 1.43% Cryptosporidium parvium [62]. In Baghdad, the highest rate of infection was 85.57% in patients who drank from contaminated water sources whereas 79.3% humans suffering from chronic infection Giardiasis [63].…”
Section: Public Health Importance Of Cryptosporidiosis and Giardiasismentioning
confidence: 99%
“…Nevertheless, the present data were higher than those recorded as 5.11%, (Morsy et al, 1991), 4.9% (Hamzy et al, 2003), 21.2% (Al-Nak kas et al, 2004), 4.57% (Ismaiel, 2011) and 16% (Babic et al, 2016. Salman et al (2016) reported that the liquid diarrhea picture in acute cases mimic that of IBS, also, the color and even the odor of the positive Giardia stool samples were the same. While in chronic giardiasis, clinical picture resemble IBD mainly epigastric pain and the other sequels.…”
Section: Resultsmentioning
confidence: 89%